The Impact of Awareness Workshops and Dialogue Sessions in Raising Social Awareness among Jordanian Youth - Alfraheed, Ahmad; A. K. Al-Banawi, Nayef (Arts and Social Sciences Series, 2026)
This study aimed to investigate the effectiveness of (awareness workshops and dialogue sessions) in raising social awareness among Jordanian youth. The study employed a mixed-methods approach (quantitative and qualitative); a questionnaire was administered to a sample of 350 male and female students participating in the center's programs. Twelve semi-structured interviews were conducted to support the interpretation of the quantitative results. The results showed that the programs were generally highly effective, with interactive activities being particularly successful. Furthermore, students' social awareness increased, especially in the areas of values related to dialogue and the rejection of hate speech. The results also indicated significant differences in some dimensions based on demographic variables.